Placental Amino Acids Transport in Intrauterine Growth Restriction - Laura Avagliano; Chiara Garò; Anna Maria Marconi (Hindawi Limited, 2012)
The placenta represents a key organ for fetal growth as it acts as an interface between mother and fetus, regulating the fetal-maternal exchange of nutrients, gases, and waste products. During pregnancy, amino acids represent one of the major nutrients for fetal life, and both maternal and fetal concentrations are significantly different in pregnancies with intrauterine growth restriction when compared to uncomplicated pregnancies. The transport of amino acids across the placenta is a complex process that includes the influx of neutral, anionic, and cationic amino acids across the microvilluos plasma membrane of the syncytiotrophoblast, the passage through the cytoplasm of the trophoblasts, and the transfer outside the trophoblasts across the basal membrane into the fetal circulation. In this paper, we review the transport mechanisms of amino acids across the placenta in normal pregnancies and in pregnancies complicated by intrauterine growth restriction.